Influence of Consumer Engagement on Word-of-Mouth: Empirical Evidence from the Tourism Industry in Vietnam - Tram, Nguyen Le Ngoc (Journal of Tourism Management Research, 2021)
The current research aims to provide an in-depth understanding of CE and its nomological network in the Vietnamese tourism service industry. To do that, data were collected from domestic visitors to Phu Quoc Island and were analyzed employing SPSS 20 and AMOS 20. The results show that, CE is considered as a construct combining psychological state and behavior intention which is inextricably interactive to behavior constructs (word-of-mouth) and psychological constructs (consumer experience, trust, and service quality). The findings reveal that different experiences and service quality during the consumption process enhance positive influences on CE, in turn, consolidating the trust of the consumer and spreading great word-of-mouth. However, the relationship between consumer trust and word-of-mouth was detected to be not significant. Besides, integrating gender in the model revealed the difference in gender do various influence the relationship between CE and its antecedents and consequences. These results reveal some important implications for marketing theory groundwork and CE literature as to how CE is conceptualized and established from a particular context and what potential antecedences and outcomes are likely to be predicted.